Collective action and property rights for poverty reduction: A review of methods and approaches - Mwangi, Esther; Markelova, Helen (Wiley, 2009)
This article provides a review of literature on the relationship between poverty and the institutions of collective action and property rights, as outlined in the conceptual framework of Di Gregorio et al. (2008). Using the elements of the framework as a guide, it offers an overview of how researchers and practitioners identify and evaluate these concepts. The article emphasises the multidimensionality of poverty and the necessity of applying various approaches and tools to conceptualising and measuring it. In addition to highlighting the crucial role that institutions play in poverty reduction, it shows power relations and the political context to be of fundamental importance in poverty‐related studies.